The X window system : programming and applications with Xt - Young, Douglas A. (PTR Prentice Hall, 1994)
Revised and updated to cover the latest release of OSF Motif, this bestselling tutorial guide to the X Window System describes how to develop interactive applications using Motif, Xlib, and Xt. More detailed explanations and examples make the second edition more accessible for novices while providing more detailed coverage of Motif for experienced programmers. Designed to provide a realistic look at how Motif applications are written, this expanded edition starts with a complete architectural overview and introduces key concepts with clear examples and working programs. Key features: covers new topics including drag and drop, tearoff menus, window manager interaction, writing Motif widgets, and XPM pixmaps; greatly expanded coverage of Motif (3 new chapters); demonstrates callbacks, event handlers, the translation manager, the resource manager, and other important Xt and Motif features; and all examples are written in ANSI C and updated to X11R5 and Motif 1.2.